1995
DOI: 10.1016/0954-6111(95)90124-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the continued supervision and asthma management knowledge of patients possessing home nebulizers

Abstract: This paper describes the results of a questionnaire survey on some aspects of nebulizer use, nebulizer instruction, and features relating to the recognition and management of deteriorating asthma. The study population consisted of 90 children with home nebulizers attending a paediatric asthma clinic, and 200 asthmatic children and 200 asthmatic adults whose nebulizers had been purchased directly from a manufacturer in the U.K. The results suggest that follow-up supervision of the patients who bought their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Despite the widespread lack of instructions on use and, above all, maintenance of home nebulizers from healthcare workers, the patients never complained. This finding has been seen in a previous study [12] and it has been shown that confidence in nebulizer use does not automatically mean that the practices were appropriate [5]. Interestingly, when healthcare workers provided more information on nebulizer use and maintenance, patients took better care of these practices.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Despite the widespread lack of instructions on use and, above all, maintenance of home nebulizers from healthcare workers, the patients never complained. This finding has been seen in a previous study [12] and it has been shown that confidence in nebulizer use does not automatically mean that the practices were appropriate [5]. Interestingly, when healthcare workers provided more information on nebulizer use and maintenance, patients took better care of these practices.…”
Section: Discussionsupporting
confidence: 73%
“…Currently, home nebulizer practice seems to be very heterogeneous among different countries [4]. In the UK, the National Health Service usually supplies home nebulizer equipment, as well as its monitoring and servicing [1]; however, the level of supervision from caregivers, generally reported to be good, seemed to be reduced when patients purchased their own home nebulizer [5]. In Italy, subjects who had been prescribed a home nebulizer by their physician purchased the device directly, while drugs for nebulization were partially or fully paid for by the National Health Service.…”
mentioning
confidence: 99%
“…Further, messages from this early look at the literature about some clinical interventions delivered at home were mixed: increased infections in children with cancer cared for at home, 8 but cheaper and equally effective chemotherapy at home; 9 infected nebulisers used for treatment of cystic fibrosis at home, [10][11][12] poorly controlled asthma with home nebulisers, 13 sometimes associated with incorrect use, 14 yet lowered emergency hospital visits and admissions when using home nebulisers for asthma; 15 higher rates of catheter infection in total parenteral nutrition (TPN) at home for children compared with adults, 16 yet less infection in central venous catheters at home than in hospital, 17 and longlasting and safe lines; 18 deep vein thrombosis, 19 embolism and septicaemia 20 in parenteral nutrition; higher rates of contamination in enteral feeds at home than in hospital 21 and poor standards of care for enteral nutrition. 22 By contrast, home ventilation therapy seemed to have a somewhat better 'press' 23,24 with suggestions that, compared with prolonged hospital care, it was both safer and cheaper.…”
Section: The Need For Evaluationmentioning
confidence: 99%
“…If they are to be used, the family should be given written instructions, which should include the need for regular cleaning and maintenance, and also the absolute necessity that rescue medication should not be administered at home any more frequently than every 4 hours. [56] A recent development is an 'intelligent nebulizer' (Halolite™) which adapts drug delivery to the child's breathing pattern, thus delivering aerosol-only inspiration, and thereby minimizing waste. Some models have a built-in microchip which allows compliance to be assessed.…”
Section: Nebulizersmentioning
confidence: 99%